Association of rs944289, rs965513, and rs1443434 in TITF1/TITF2 with Risks of Papillary Thyroid Carcinoma and with Nodular Goiter in Northern Chinese Han Populations. (11th February 2020) - Zhang, Xin; Gu, Yulu; Li, Yong; Cui, Heran; Liu, Xiaoli; Sun, Hui; Yu, Qiong; Yu, Yaqin; Liu, Yawen; Zhan, Siyan; Cheng, Yi
Abstract : Objective . In this study, we aimed to investigate the associations of three single-nucleotide polymorphisms (SNPs) on TITF1/TITF2 (rs944289, rs965513, and rs1443434) with susceptibility to papillary thyroid carcinoma (PTC) and with nodular goiter (NG) in northern Chinese Han populations. Methods . We performed a case-control study comprising 861 PTC patients, 562 NG patients, and 896 normal controls (NCs). One TITF1 SNP (rs944289) and two TITF2 SNPs (rs965513 and rs1443434) were genotyped. Departures from Hardy–Weinberg equilibrium (HWE) in the control group were evaluated using chi-square test. Associations of the SNPs with PTC and with NG were assessed by unconditional logistic regression using the online SNPStats program. Bonferroni correction was performed for multiple tests in genotype analyses. Data analysis was performed by SPSS24.0 unless otherwise specified. Results . For rs944289, T allele was associated with increased risks for both PTC (OR = 1.23, 95% CI: 1.08–1.41, P = 0.002 ) and NG (OR = 1.28, 95% CI: 1.10–1.50, P = 0.002 ), and TT genotype significantly increased NG risk (recessive model, OR = 1.60, 95% CI: 1.22–2.10, P = 0.001 ). For rs965513, no association was observed after Bonferroni correction. For rs1443434, G allele was associated with increased PTC risk (OR = 1.33, 95% CI: 1.10–1.61, P = 0.003 ). Moreover, PTC risk increased with the number of total risk alleles of the three SNPs (OR = 1.25, 95% CI: 1.13–1.37, P < 0.001 ). After stratified by gender, the risk effect of rs944289 T allele on PTC was only observed in females (OR = 1.29, 95% CI: 1.10–1.50, P = 0.001 ). Individuals carrying rs944289-rs965513-rs1443434 haplotypes T-G-G and T-G-T had increased risks of PTC (OR = 1.82, 95% CI: 1.25–2.64, P = 0.002 ) and NG (OR = 1.28, 95% CI: 1.06–1.54, P = 0.011 ), respectively. Conclusions . There are associations of rs944289 and rs1443434 polymorphisms with PTC risk and association of rs944289 polymorphism with NG risk. Haplotypes T-G-G and T-G-T are risk haplotypes of PTC and NG, respectively.